2014
DOI: 10.3389/fnint.2014.00048
|View full text |Cite
|
Sign up to set email alerts
|

Monetary reward speeds up voluntary saccades

Abstract: Past studies have shown that reward contingency is critical for sensorimotor learning, and reward expectation speeds up saccades in animals. Whether monetary reward speeds up saccades in human remains unknown. Here we addressed this issue by employing a conditional saccade task, in which human subjects performed a series of non-reflexive, visually-guided horizontal saccades. The subjects were (or were not) financially compensated for making a saccade in response to a centrally-displayed visual congruent (or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 68 publications
6
22
0
Order By: Relevance
“…Our next stage of analysis was to examine differences in eye movement parameters between groups. The major focus of interest was peak velocity, a marker of invigoration of response which has been shown to be sensitive to rewards in both human and monkey studies ( Chen et al , 2013 , 2014 ; Manohar et al , 2015 ). We also analysed reaction times and saccadic variability, which are discussed later.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our next stage of analysis was to examine differences in eye movement parameters between groups. The major focus of interest was peak velocity, a marker of invigoration of response which has been shown to be sensitive to rewards in both human and monkey studies ( Chen et al , 2013 , 2014 ; Manohar et al , 2015 ). We also analysed reaction times and saccadic variability, which are discussed later.…”
Section: Resultsmentioning
confidence: 99%
“…Parkinson’s disease patients often suffer from executive deficits ( Dirnberger and Jahanshahi, 2013 ; Gratwicke et al , 2015 ). The use of physiological measures like pupillometry to index value placed on monetary incentives minimizes executive function requirements ( Hong and Hikosaka, 2008 ; Chen et al , 2014 ; Rudebeck et al , 2014 ; Manohar and Husain, 2015 ; Manohar et al , 2015 ). Our findings suggest that apathetic Parkinson’s disease patients place less value on rewards in the evaluation stage of goal-directed action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider that we find minimizing the errors of our memory intrinsically rewarding. Indeed, extrinsic rewards influence the metrics of saccades in humans and monkeys (Chen, Chen, Zhou, & Mustain, 2014;Takikawa, Kawagoe, Itoh, Nakahara, & Hikosaka, 2002). For instance, extrinsic rewards affect both the velocity of saccades as well as neural activity in dopamine-associated reward circuits (Kato et al, 1995), and they modulate neural activity in cortical areas that represent the goals of saccade plans (Platt & Glimcher, 1999).…”
mentioning
confidence: 99%
“…Shorter reaction times to rewarding stimuli indeed suggest that we prioritise the preparation of more rewarding actions. Work on humans (Chen LL et al, 2014;Manohar SG et al, 2017;Xu-Wilson M et al, 2009) and non-human primates (Bendiksby MS and Platt ML, 2006;Hikosaka O, 2007;Lauwereyns J et al, 2002;Takikawa Y et al, 2002) has shown that saccades are faster to stimuli associated with relatively larger rewards and their trajectories are biased towards previously rewarded locations (e.g. Hickey C and van Zoest W, 2012;Theeuwes J and Belopolsky AV, 2012).…”
Section: Introductionmentioning
confidence: 99%